Upaya Hukum Penyelesaian Sengketa Barang Milik Negara Berupa Aset Tanah Pangkalan Udara - Firman Wijaya; Abdul Atik; Diah Turis Kaemirawati (Wajah Hukum, 2022)
Based on Government Regulation No. 27 of 2014 on The Management of State/Regional Property, Users of Goods / Power of Goods Users are authorized and responsible in securing and maintaining State Property (BMN) which is in its control. Land problems in the Indonesian Air Force (TNI AU) of Srimulyono Herlambang (SMH) area in Palembang cannot be handed over to the community or removed from state property records, unless there has been a court decision with permanent legal force and get permission from the Ministry of Finance. This research aims to find out how the procedures in land use based on Government Regulation Number 27/2014 as well as the resolution of disputes over land rights of State Property at Sri Mulyono Herlambang (SMH) Air Base in Palembang. The research method used is a case study. The results of the research revealed that the Physical Use of Land by the Indonesian Air Force is that the TNI AU Cq. Sri Mulyono Herlambang Air Base has controlled the physical area of 260 ha in Sukarami Village, but the Owner's (community) has controlled the physical land for more than 20 years and there has been a basis of rights from the owner's in the form of land certificates from the Village Head / Lurah and camat that can be used as the legal basis for applying for the right to obtain a certificate of property rights for the land he controlled at the Land Office of Palembang City.